2021
DOI: 10.1002/adfm.202110423
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Platinum and Gold Nanoparticles in Oxygen Activation for Enhanced Room‐Temperature Formaldehyde Oxidation

Abstract: Room-temperature oxidation over supported noble metals provides a feasible approach to eliminating formaldehyde (HCHO) from indoor air. Oxygen activation by noble metals such as gold and platinum plays a key role in achieving complete HCHO oxidation, but it is unclear how different noble metals function synergistically toward oxygen activation. Here, the synergistic mechanisms of Pt and Au nanoparticles (NPs) coloaded on TiO 2 in catalytic HCHO oxidation are elucidated. Strikingly, ≈0.08% doping of Pt can dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 57 publications
(38 reference statements)
1
17
1
Order By: Relevance
“…Regardless, only a small portion of unlabeled acids was found, indicating that dissolved oxygen did not react directly with dissolved organics in this reaction. In the gas phase, platinum is known to dissociate molecular oxygen into two oxygen atoms that incorporate into the aldehyde to form a carboxylate on the surface, but this reaction is inconsistent with our observation of the origin of the oxygen atoms in the product.…”
Section: Resultscontrasting
confidence: 87%
“…Regardless, only a small portion of unlabeled acids was found, indicating that dissolved oxygen did not react directly with dissolved organics in this reaction. In the gas phase, platinum is known to dissociate molecular oxygen into two oxygen atoms that incorporate into the aldehyde to form a carboxylate on the surface, but this reaction is inconsistent with our observation of the origin of the oxygen atoms in the product.…”
Section: Resultscontrasting
confidence: 87%
“…Cu ions were immobilized within the amorphous precipitate. Subsequently, the generated unstable • H 2 NCH 2 radicals were oxidized quickly by ferrate (e.g., Fe(V)) and decomposed into formaldehyde (HCHO) and ammonia (NH 3 ) (R2). , Eventually, formaldehyde was further oxidized into formate (HCOO – ) (R3), while ammonia was converted into (NO 3 – ) or nitrite (NO 2 – ) (R4–R9) . These end degradation products have been identified by the IC method in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, it was hard to track the dynamic process of CuGly decomposition due to the too fast reaction rates. Nevertheless, major chemical reactions (R1–R9 in both Figure and Table ) could be proposed based on the identification of degradation products in the current study and the findings reported in previous studies. …”
Section: Resultsmentioning
confidence: 99%
“…Many supported noble metal catalysts have been extensively investigated because of their excellent low-temper-ature catalytic activity. [8][9][10][11] Their rarity and expensive cost, however, limit their further applications. In recent years, transition metal oxide catalysts, including MnO 2 , Co 3 O 4 , CeO 2 , Fe 2 O 3 , TiO 2 , and metal oxide composites have aroused intense interest due to their appealing activity and low price.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the catalysts suitable for the catalytic oxidation of low‐concentration and high‐throughput formaldehyde at room temperature still remain to be developed. Many supported noble metal catalysts have been extensively investigated because of their excellent low‐temperature catalytic activity [8–11] . Their rarity and expensive cost, however, limit their further applications.…”
Section: Introductionmentioning
confidence: 99%